Peranan Camat Dalam Meningkatkan Kinerja Pegawai di Kantor Camat Percut Sei Tuan - Lubis, Ahmad Fadhil; Lubis, Yurial Arief (Universitas Medan Area, 2025)
The sub-district head has a strategic role in improving the performance of employees at the sub-district level to support the effectiveness of government administration and public services. This study aims to analyze the role of the sub-district head in improving employee performance at the Percut Sei Tuan Sub-district Office, Deli Serdang Regency, as well as identify the inhibiting factors in the implementation of the policy. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The research informants consisted of the sub-district head, the secretary of the sub-district, the head of the general and personnel subdivision, as well as employees and the community as additional informants. The results of the study show that the sub-district has implemented various strategies to improve employee performance, including performance supervision, motivation, improvement of work discipline, and training and skill development of employees. However, several obstacles hinder the effectiveness of the role of the sub-district, such as low employee discipline, lack of work facilities, lack of training programs, weak communication and coordination systems, and budget limitations. This obstacle affects the efficiency of employee work and the quality of public services.